2007
DOI: 10.1038/nature05882
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Sheep don’t forget a face

Abstract: Nature 414, 165-166 (2001) In Fig. 1b of this Brief Communication, the legend and text did not make it clear that two different groups of ten sheep were used in the study to give overall n 5 20. A reanalysis of the data using a post-hoc Tukey test (rather than a paired t-test, as originally stated) revealed some small errors that altered the significance values slightly; however, there is no overall change in the results. The maximum retest interval was 801 rather than 800 days, and 100-500 trials were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Sheep are an accessible experimental species and have been used extensively to model a number of neurological conditions, including non-accidental head injury (Sandoz et al, 2012; Anderson et al, 2014), TBI (Vink et al, 2008; Vink et al, 2017), and Huntington’s Disease (Reid et al, 2013; Morton et al, 2014). Although sheep have earned a reputation as unintelligent animals, the evidence is quite to the contrary, as sheep demonstrate excellent facial recognition, executive decision making and emotional processing, often comparable to humans on equivalent tasks (Tate et al, 2006; Keith et al, 2007; Morton and Avanzo, 2011). Specifically, the high proportion of white to gray matter in the sheep brain is of particular benefit when studying the pathophysiology of edema and ICP, given that edematous fluid accumulates in the white matter following ischaemic stroke (Jha, 2003; Mahajan and Bhagat, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sheep are an accessible experimental species and have been used extensively to model a number of neurological conditions, including non-accidental head injury (Sandoz et al, 2012; Anderson et al, 2014), TBI (Vink et al, 2008; Vink et al, 2017), and Huntington’s Disease (Reid et al, 2013; Morton et al, 2014). Although sheep have earned a reputation as unintelligent animals, the evidence is quite to the contrary, as sheep demonstrate excellent facial recognition, executive decision making and emotional processing, often comparable to humans on equivalent tasks (Tate et al, 2006; Keith et al, 2007; Morton and Avanzo, 2011). Specifically, the high proportion of white to gray matter in the sheep brain is of particular benefit when studying the pathophysiology of edema and ICP, given that edematous fluid accumulates in the white matter following ischaemic stroke (Jha, 2003; Mahajan and Bhagat, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Even juvenile pigs can discriminate equally familiar conspecifics (58) and they may use their knowledge to adjust their foraging tactics to whom they are with (59). However, the extent to which individual recognition of all group members is plausible in groups of 50 or more individuals, as is the case in sheep (60), is unknown. Fraser and Broom (61) estimated that pigs may recognise between 20 and 30 counterparts and Verdon and Rault (62) suggested that individual recognition might be less likely in unnaturally large group sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep are also commonly used as cardiovascular models for applying artificial replacement devices [ 32 ] and also in studies of female fertility and pregnancy disorders [ 33 , 34 ]. Other relevant works in the field of cognition have allowed to realize that sheep can be good models of study in the mechanisms of decision-making, facial recognition and triggering emotions [ 35 , 36 , 37 ]. The genome of the domestic sheep has already been sequenced, unlike that of the goat.…”
Section: Introductionmentioning
confidence: 99%